2015
DOI: 10.1007/s10014-015-0218-4
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic study of methionine positron emission tomography in patients with glioblastoma with oligodendroglial components

Abstract: Anaplastic oligoastrocytoma (AOA) with necrosis is classified as glioblastoma (GBM) with oligodendroglioma component (GBMO), according to the 2007 World Health Organization classification. The prognosis of GBMO remains controversial because definitive diagnostic criteria regarding the percentage of the oligodendroglial components (OC) in the GBM do not exist. We previously reported dynamic methionine (MET) positron emission tomography (PET) in patients with these tumors. A significant decrease in the MET signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Moreover, the dynamic acquisition of 11 C-MET is not so demanding for patients, nor as time-consuming, lasting about 20 min (vs. 60 min for 18 F-FET). Unlike fluorinated aminoacid radiotracers, kinetic 11 C-MET parameters in glioma grading/diagnosis have been evaluated by few authors, finding controversial results [30,32,33]. As already pointed out, no data are available on the prognostic role of dynamic 11 C-MET PET parameters in glioma recurrent patients.…”
Section: Kinetic Met-pet Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the dynamic acquisition of 11 C-MET is not so demanding for patients, nor as time-consuming, lasting about 20 min (vs. 60 min for 18 F-FET). Unlike fluorinated aminoacid radiotracers, kinetic 11 C-MET parameters in glioma grading/diagnosis have been evaluated by few authors, finding controversial results [30,32,33]. As already pointed out, no data are available on the prognostic role of dynamic 11 C-MET PET parameters in glioma recurrent patients.…”
Section: Kinetic Met-pet Parametersmentioning
confidence: 99%
“…Recently, Zagori et al [29] explored the usefulness of dynamic 18 F-DOPA parameters in the prognostication of patients with suspected glioma recurrence, failing to prove the definitive primacy of these indices compared to static ones. Dynamic 11 C-MET parameters have been studied in the differential diagnosis of brain tumours [30,31] to characterise glioblastoma with an oligodendroglial component [32] and to distinguish highgrade from low-grade glioma (LGG) [33], reaching conflicting results. Since differences in uptake mechanism are present among amino-acids radiotracers, the findings observed for dynamic 18 F-FET and 18 F-DOPA in the prognostic evaluation cannot directly be translated to 11 C-MET.…”
Section: Introductionmentioning
confidence: 99%
“…Second, while we only included patients who underwent the same PET/CT protocol at our hospital, the textural features of PET depend on the image acquisition conditions, with different acquisition modes and reconstruction parameters potentially influencing the results [23]. Third, oligodendroglial cell differentiation may influence MET uptake [4,24], although we were unable to evaluate this factor because of the limited number of patients. Further clinical studies are needed to address these issues and to confirm whether TA provides prognostic value in the clinical management of gliomas.…”
Section: Limitationsmentioning
confidence: 99%
“…A significant dynamic increase of MET T/N ratios was also observed in GBM and central nervous system lymphoma, 29) which are often indistinguishable on MRI to the extent that additional clinical data and other diagnostic modalities are required. Next, we performed dynamic MET-PET studies on GBM patients with oligodendroglial components (GBMO), 30) whose prognoses remain controversial to date. This GBMO study showed that the dynamic MET signal tended to decrease over time; these changes resembled those in the above-mentioned oligodendroglial tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, GBMO may be a possible differential diagnosis when dynamic MET-PET shows a decreasing pattern. 30) …”
Section: Introductionmentioning
confidence: 99%